Rohdea rotiformis (Asparagaceae), a new species from Northern Sichuan, China - Feng, Hui Zhe; Liu, Ming; Li, Xue Yu; Liu, Xiao; Liu, Lin (Phytotaxa, 2023)
Rohdea rotiformis is described and illustrated as a new species from Sichuan province of China. The new species possesses a cushionlike, ringed, fleshy appendage above the stamens in perianth throat. In these features, the new species is morphologically similar to R. urotepala but differs in its ringed appendage surface smooth without verruculose.